Thyroid Swellings Undergoing Thyroidectomy in a Tertiary Hospital of Nepal: A Retrospective Study of Distribution and Prevalence of Malignancy - Gupta, Mudit; Mahaseth, Rajeev Kumar; Khadgi, Sajish; Shrestha, Asmita; Bhat, Neeti; Karna, Alina (Nepal Journal of Health Sciences, 2021)
Introduction: Thyroid nodules brought to a hospital are checked for cancer. A post-operative histological examination is a gold standard for diagnosing thyroid lesions. Treatment is aided by a prior understanding of the disease’s underlying pattern.Objective: A retrospective study was done to determine the prevalence and distribution of malignancy in suspicious thyroid nodules.Methods: The study was conducted at Ganesh Man Singh Memorial Academy of ENT- Head and Neck studies from August 2017 to March 2020. All the subjects (n=183) presenting with a thyroid nodule and who had post-operative histopathological evaluation available were recruited in the study. The proportion and percentage of findings of Fine Needle Aspiration Cytology (FNAC) and histopathological evaluation were done. The distribution of histopathological observation was also analyzed in terms of age group and gender.Results: The mean age of study participants was 40.23 ± 13.77 years (n=183). The predominance of women was notable. In about 98 (53.55%) of the patients who underwent thyroidectomy, a benign lesion was found, but the most common finding was papillary carcinoma (40.98%). In the age group below 50 years, papillary carcinoma was most common. Among people older than 50, colloid goiter was more common. Follicular and medullary carcinomas were only observed in female participants. Gender did not appear to be associated with malignancy (p=0.99). Follicular adenomas were noted to have the youngest mean age.Conclusions: We observed a high prevalence of malignancy, particularly papillary carcinoma in clinically suspected thyroid nodules of a tertiary hospital in Nepal.Keywords: Colloid Goiter; malignancy; papillary carcinoma; thyroid cancer; thyroid nodule.